2013
DOI: 10.1111/cfs.12098
|View full text |Cite
|
Sign up to set email alerts
|

The roles of social support and family resilience in accessing healthcare and employment resources among families living in traditional public housing communities

Abstract: This study relied on theories of family resilience to examine and differentiate the roles of community social support and family resilience in regards to access and utilization of healthcare and employment resources for public housing residents. The study assessed 234 public housing residents and used structured regressions to test the role of family resilience, internal and external community social support on outcomes associated with economic mobility. Results suggest that external community social support i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…That being said, individual resourcefulness does matter for individuals lacking within-community resources. For example, Distelberg and Taylor (2013) found that residents in public housing communities who exhibited higher levels of resilience sought social support from outside of their communities to a greater degree, thereby increasing their access to and use of resources. This finding is consistent with Yehuda's definition of resilience (see Southwick et al 2014), which includes the individual's ability to utilize available adaptive capacities.…”
Section: Family and Community Resilience And The Transactional Model mentioning
confidence: 99%
“…That being said, individual resourcefulness does matter for individuals lacking within-community resources. For example, Distelberg and Taylor (2013) found that residents in public housing communities who exhibited higher levels of resilience sought social support from outside of their communities to a greater degree, thereby increasing their access to and use of resources. This finding is consistent with Yehuda's definition of resilience (see Southwick et al 2014), which includes the individual's ability to utilize available adaptive capacities.…”
Section: Family and Community Resilience And The Transactional Model mentioning
confidence: 99%
“…The importance of social support has also been identified indirectly (Fauth, Leventhal, & Brooks-Gunn, 2008;Leventhal & Brooks-Gunn, 2003) and directly (Distelberg & Taylor, 2013) in studies of similar HUD initiatives.…”
Section: Factors Predictive Of Self-sufficiencymentioning
confidence: 99%
“…Although most of these initiatives offer better access to resources needed for economic mobility, such benefits often come at the cost of existing familial and community relationships (Fauth et al, 2008;Leventhal & Brooks-Gunn, 2003;Distelberg & Taylor, 2013). Furthermore, in a recent evaluation of public housing community residents, Distelberg and Taylor (2013) point out that family resilience is a key component to HUD families achieving socioeconomic mobility, and social support within a community helps increase a family's resilience.…”
Section: Work-oriented Welfare Originsmentioning
confidence: 99%
“…As noted above the current trends in housing assistance socioeconomic mobility programs are quite low (with roughly a 25% success rate) (USDHUD, 2008(USDHUD, , 2011. Within these same studies, as well as additional independent studies (Bowie et al, 2007;Distelberg & Taylor, 2013;Theodos et al, 2010) it has been noted that better (robust and evidenced-based) measures would help both government and nongovernment program evaluators assess the role of multiple levels of resilience factors in the pursuit of socioeconomic mobility. To that end we evaluated the IFCR's ability to predict the employment and educational level of participants.…”
Section: Discussionmentioning
confidence: 93%
“…Although this finding is novel to the housing field, it is well studied in other social science fields. In this case resilience, especially resilience framed in an ecological conceptual framework, has been seen to help various individuals and families reach greater levels of socioeconomic mobility (Collard, 2010;Distelberg & Taylor, 2013;Johnson, Honnold, & Threlfall, 2011;Keene & Geronimus, 2011;Meschede, 2010;Noone & Patterson, 2010;Tester, Ruel, Anderson, Reitzes, & Oakley, 2011;Theodos, Popkin, Guernsey, & Getsinger, 2010). It is also important to note that in a recent evaluation of the welfare to work program, Bowie, Barthelemy, and White (2007) found some benefit to socioeconomic mobility programs in relationship to housing assistance programs, but they also noted a need for future evaluations to include more robust measurements for concepts in line with a resilience conceptual framework.…”
Section: Introductionmentioning
confidence: 99%